ترويج صورة الوجهة السياحية الجزائرية ضمن المخطط التوجيهي للتهيئة السياحية Sdat 2030 الديوان الوطني للسياحة (ont) نموذجا - حمي, عزاز; حساني, رقية (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إبراز الجهود التي تقوم بها الدولة الجزائرية من خلال للمخطط التوجيهي للتهيئة السياحية SDAT 2030 بهدف ترويج الوجهة السياحية الجزائرية وفق منهجية تعتمد على تثمين وجهةالجزائرقصدالجعلمنهاملتقىسياحي للامتياز،و تسليط الضوء على الدور الذي يلعبه الديوان الوطني للسياحة كهيئة عمومية مكلفة بالترويج للوجهة السياحة الجزائرية و ترقيتها ، حيث خلصت الدراسة أن الديوان الوطني للسياحة يستعمل وسائل ترويجية مختلفة ويقوم بنشاطات متعددة للوصول الى أهدافه المسطرة، و بعد عرض بعض المؤشرات السياحة سجلنا تطورا في السياحة الوافدة في الجزائر خلال الفترة 2015-2018 مع تسجيل تراجع خلال سنتي 2019 و 2020 نظرا للظروف السياسية التي عرفتها البلاد و تداعيات أزمة كورونا كوفيد 19 على السياحة الدولية، لكن تبقى الوجهة السياحية الجزائرية تحتل مراكز متأخرة مقارنة بدول شمال إفريقيا لاسيما المغرب، تونس و مصر . This study aims to highlight the efforts undertaken by the Algerian state through the SDAT 2030 tourism development guideline with the aim of promoting the Algerian tourist destination according to a methodology based on valuing the destination of Algeria in order to make it a tourist forum for excellence, and to shed light on the role played by the National Tourism Office as a public authority in charge By promoting and promoting the destination of Algerian tourism, the study concluded that the National Tourism Office uses various promotional means and performs multiple activities to reach its established goals. And 2020, given the political conditions that the country has known and the repercussions of the Corona Covid 19 crisis on international tourism, but the Algerian tourist destination remains lagging compared to North African countries, especially Morocco, Tunisia and Egypt.
Keywords: الترويج السياحي، السياحة ،الوجهة السياحية الجزائرية ، المخطط التوجيهي للتهيئة السياحية ، الديوان الوطني للسياحة. ; Tourism Promotion, Tourism, Algerian Tourist Destination, Tourism Development Master PlanNational Tourism Office.